(untitled) - Lowery, Gwen (New York, 2001)
Here's a winning combination: a series of successful project management strategies that cover every phase of the process AND an insider's guide to the most powerful and versatile project management software available anywhere. That's what you'll find in Managing Projects with Microsoft Project 2000.
Keywords: Project management,Quản trị dự án; Computer programs,Chương trình máy tính